Les vêpres siciliennes - Verdi, Giuseppe 1813-1901 (Opus Arte, 2011)
Verdi's romantic tragedy of tensions between private passions and public politics set in Sicily, in this production in the 1940s; includes the full Four Seasons ballet in Act III.
Interpr. u.a.: Alejandro Marco-Buhrmester [Guy de Montfort]. Burkhard Fritz [Henri]. Balint Szabo [Jean Procida]. Barbara Haveman [Duchess Hélène]. Livia Aghova [Ninetta]. Jeremy White [Le Sire de Béthune]. Christophe Fel [Le Comte de Vaudemont]. Chorus of the Netherlands Opera. Martin Wright [Choreinstud.]. Netherlands Philharmonic Orchestra. Paolo Carignani [Dir.]. Christof Loy [Bühnenregie]. Evita Galanou ; Thomas Wollenberger [Filmregie]. - Aufn.: Amsterdam, Het Muziektheater, 23. und 29. September 2010. - Franz. gesungen. - Untertitel: engl., franz., dt., span. - Enth. Bonusmaterial: Introduction to Les vêpres siciliennes; Cast gallery
Keywords: Verdi, Giuseppe / 1813-1901 / Film adaptations; World War, 1939-1945 / Campaigns / Italy / Sicily / Drama; Man-woman relationships / Drama; Weltkrieg (1939-1945); Italien; DVD-Video